The Role of Animated Characters in the Socialization of Children in the Russian Federation - Kabdullinovna Tanatova, Dina; Vladimirovich Korolev, Ivan; Vladimirovna Nevskaya, Marina; Rafaelevna Tairova, Liliya (International Journal of Engineering and Technology, 2018)
The studies of animated characters as a factor of socialization have virtually no theoretical or empirical interpretation in the Russian sociology. At the same time, cartoons have a huge potential for development and successful socialization of children. It is a well-known fact that animated films are widely used in pedagogy, psychology, and within the family circle. The public especially favors cartoons produced during the Soviet period, but gradually they become a thing of the past. This process is mainly due to the fact that visually and technologically they are inferior to modern cartoons and thus lose their appeal. As a result of the availability of the Internet and Smart TV, the number of young users watching videos and TV broadcasts has risen significantly. The leaders of ratings in terms of views and popularity are cartoons made in the USA, which reflect the values and characteristics of Western society. However, modern animated films boast a wide range of genres, plots, and characters created with the help of new technologies. Their pedagogical, cultural, and development potential is impressive, and their role in the socialization of children is still significant. Â Â Â